A nationwide study of occurrence and exposure assessment of neonicotinoid insecticides and their metabolites in drinking water of China. (1st February 2021) - Mahai, Gaga; Wan, Yanjian; Xia, Wei; Wang, Aizhen; Shi, Lisha; Qian, Xi; He, Zhenyu; Xu, Shunqing
Highlights: Seven NNIs and metabolites were frequently detected in drinking water High levels of NNIs and IMIeq were found in surface water derived tap water NNI levels and patterns varied in different regions and according to water sources NNIs in 16 drinking water samples exceeded the guideline recommended by the EU Drinking water ingestion is a significant exposure pathway of NNIs in China Abstract: Neonicotinoid insecticides (NNIs) are the most extensively used insecticides worldwide, threatening ecosystem and human health. However, nationwide studies of NNIs and their metabolites in drinking water are limited. In order to characterize the contamination status of NNIs in drinking water throughout China, we collected 884 drinking water samples including 789 tap water and 95 groundwater samples from 32 provinces (covering seven regions of mainland China: south, central, east, north, northeast, northwest, and southwest) and Hong Kong. Ten NNIs and six of their main metabolites were determined in the water samples. The relative potency factor method was used to assess the cumulative concentrations of NNIs and their metabolites (imidacloprid-equivalent total NNIs, IMIeq ) based on the chronic reference doses (cRfDs) of the NNIs or the toxic effects of the mataboilites. The IMIeq varied among the studied regions, with a median concentration of 24.5 ng/L and a maximum concentration of 8, 622 ng/L. The predominant NNIs in drinking water were acetamiprid (ACE) and imidacloprid (IMI). Compared with tap water derived from groundwater, much higher concentrations of IMIeq and NNIs were found in tap water derived from surface water. Different concentrations and patterns of NNIs in drinking water were observed in different regions, provinces, and capital cities, mainly due to regional and provincial differences in crop types and volumes of pesticide usage. The concentrations of NNIs in the drinking water of provincial capitals and small/medium cities were higher than the concentrations in rural areas. The estimated daily intake (EDI) of IMIeq was at least two orders of magnitude lower than the cRfD of IMI, while the NNIs in 16 drinking water samples exceeded the acceptable value (100 ng/L) recommended by the European Union. This study provided a nationwide profile of the occurrence of NNIs and their metabolites in the drinking water of China and the associated potential cumulative human health risks, taking into account of the toxicity differences between NNIs and their metabolites. Graphical abstract: Image, graphical abstract